Edvard Munch : behind the Scream - Prideaux, Sue (Yale University Press, 2005)
Although almost everyone recognizes Edvard Munch's famous painting The Scream, hardly anyone knows much about the man. What kind of person could have created this universal image, one that so vividly expressed all the uncertainties of the twentieth century? What kind of experiences did he have? In this book, the first comprehensive biography of Edvard Munch in English, Sue Prideaux brings the artist fully to life. Combining a scholar's precision with a novelist's insight, she explores the events of his turbulent life and unerringly places his experiences in their intellectual, emotional, and spiritual contexts. With unlimited access to tens of thousands of Munch's papers, including his letters and diaries, Prideaux offers a portrait of the artist that is both intimate and moving. Munch sought to paint what he experienced rather than what he saw, and as his life often veered out of control, his experiences were painful. Yet he painted throughout his long life, creating strange and dramatic works in which hysteria and violence lie barely concealed beneath the surface. An extraordinary genius, Munch connects with an audience that reaches around the world and across more than a century.